Identifikasi Hama Dan Penyakit Pada Tanaman Sedap Malam Menggunakan Metode K-Nearest Neighbor - Ikhlasul Amal Faj'r; Nurul Hidayat; Donald Sihombing (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Tuberose (Polianthes Tuberose) is one of the ornamental plants that comes from the family Agavaceae which has many benefits. But in the cultivation found several obstacles, including pests and diseases that are very influential on growth and flower production. To facilitate farmers to identify pests and diseases, then needed a system, one of the methods that can be used is k-nearest neighbor. After the implementation and testing, the results obtained with the highest accuracy of 94%. Thus, it can be concluded that k-nearest neighbor algorithm on pest and plant flower diseases identification system can be applied well so that it is very beneficial for tuberose flower farmers.